2019
DOI: 10.1001/jamanetworkopen.2019.16318
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Marijuana Use and Risk of Cancer

Abstract: This systematic review and meta-analysis assesses the association of marijuana use with the development of cancer in adults with at least 1 joint-year exposure (equivalent to 1 joint per day for 1 year).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 78 publications
(140 reference statements)
1
103
0
Order By: Relevance
“…“Study populations were young, and few studies measured longitudinal exposure. The included studies were often limited by selection bias, recall bias, small sample of marijuana-only smokers, reporting of outcomes on marijuana users and tobacco users combined, and inadequate follow-up for the development of cancer…Most studies poorly assessed exposure, and some studies did not report details on exposure, preventing meta-analysis for several outcomes.”198…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Study populations were young, and few studies measured longitudinal exposure. The included studies were often limited by selection bias, recall bias, small sample of marijuana-only smokers, reporting of outcomes on marijuana users and tobacco users combined, and inadequate follow-up for the development of cancer…Most studies poorly assessed exposure, and some studies did not report details on exposure, preventing meta-analysis for several outcomes.”198…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were often limited by selection bias, recall bias, small sample of marijuana-only smokers, reporting of outcomes on marijuana users and tobacco users combined, and inadequate follow-up for the development of cancer…Most studies poorly assessed exposure, and some studies did not report details on exposure, preventing meta-analysis for several outcomes." 198 Example of item 23c of PRISMA 2020 checklist "Because of time constraints…we dually screened only 30% of the titles and abstracts; for the rest, we used single screening. A recent study showed that single abstract screening misses up to 13% of relevant studies (Gartlehner 2020).…”
Section: Essential Elementsmentioning
confidence: 99%
“…In addition to worsening the clinical outcome (especially involving respiratory risk) [10], cannabis use can generate or increase psychiatric disorders (mainly psychotic symptoms) [11], intense emotional and behavioral reactions were reported during the pandemic, such as fear, boredom, loneliness, anxiety, insomnia, anger and aggression [12]. These symptoms might be especially intense in people who use cannabis, as it is a population that has high rates of psychiatric comorbidities, is particularly sensitive to dysphoric emotional states and has a low tolerance for frustration and stress [13].…”
Section: Open Accessmentioning
confidence: 99%
“…A recent systematic review compared rates of all cancer types in cannabis users (defined as ≥ 1 joint‐year exposure) compared with non‐users [32]. Eight studies assessing the association of cannabis‐smoking and lung cancer were included.…”
Section: Epidemiologymentioning
confidence: 99%